2012
DOI: 10.1080/10807039.2012.672892
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Point Source Brine Discharge into a Riverine System and Implications for TDS Limitations

Abstract: The North Fork Holston River (NFHR) below Saltville, Virginia, has been the subject of many studies due to years of contamination from a closed chloroalkali plant. In addition, a point source brine discharge high in total dissolved solids (TDS) may also be adversely affecting aquatic biota. This study assessed the toxicity of the brine discharge to selected test organisms, including two freshwater mussel species and also discusses implications for development of a TDS limit based on brine toxicity. Ceriodaphni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This could be explained by the fact that the subhaline ponds were stocked with the fish that are required for the development of its glochidia and are a good vector for its dispersion (Pip 1986). All of the life stages of unionid mussels are sensitive to an elevated content of chlorides (Bringolf et al 2007), but glochidia are particularly sensitive to acute exposure (Gills 2011; Echols et al 2012;Patnode et al 2015). Beggel and Geist (2015) found that a chloride concentration above 5962 mg L −1 caused the death of A. anatina glochidium in laboratory conditions, whereas according to Canadian Water Quality Guidelines for the Protection of Aquatic Life (2011), the short-term exposures to chloride levels above 640 mg L −1 may pose the greatest toxic effects on glochidia of certain freshwater mussel species (CCME 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that the subhaline ponds were stocked with the fish that are required for the development of its glochidia and are a good vector for its dispersion (Pip 1986). All of the life stages of unionid mussels are sensitive to an elevated content of chlorides (Bringolf et al 2007), but glochidia are particularly sensitive to acute exposure (Gills 2011; Echols et al 2012;Patnode et al 2015). Beggel and Geist (2015) found that a chloride concentration above 5962 mg L −1 caused the death of A. anatina glochidium in laboratory conditions, whereas according to Canadian Water Quality Guidelines for the Protection of Aquatic Life (2011), the short-term exposures to chloride levels above 640 mg L −1 may pose the greatest toxic effects on glochidia of certain freshwater mussel species (CCME 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Total Dissolved Solids (TDS) is a parameter used to determine solid particles or substances dissolved in water, both organic and inorganic 23 . The high TDS value shows a negative relationship with several parameters of the aquatic environment it can increase the toxicity of the organisms in it 24 Based on Table 1. the result data obtained from day 0 to day 30 the average TDS value in the Ciujung River water sample has increased.…”
Section: Total Dissolved Solids (Tds)mentioning
confidence: 99%